Contaminated and derelict land the proceedings of Green 2 : the second international symposium on geotechnics related to the environment held in Krakow Poland, September 1997 - Sarsby, R. W. (Thomas Telford, 1998)
These papers focus on the problems of contaminated and derelict land, and look at site characterisation and assessment. Material properties and measurement are discussed, as well as treatment of contamination, and containment of pollution.